A Novel Thermocell System Using Proton Solvation Entropy. Issue 13 (15th December 2020) - Kobayashi, Takashi; Yamada, Teppei; Tadokoro, Makoto; Kimizuka, Nobuo
Abstract: The entropy change associated with proton‐coupled electron transfer (PCET) reactions significantly enhance the Seebeck coefficient ( S e ) of thermocells. A redox pair of [Ru(H x im)6 ] 2+/3+ (Him=imidazole, x= 0≈1) releases three protons in their one‐electron redox reactions in thermocells, which gave a remarkably high S e of −3.7 mV K −1 as confirmed by temperature‐dependent square wave voltammetry. The value of S e is proportional to the redox reaction entropy (Δ S rc ), which increased with the number of dissociating protons. This result demonstrates the utility of PCET reaction toward efficient thermoelectric conversion. Abstract : Large redox entropy of proton‐coupled electron transfer reaction was utilized for thermoelectric energy conversion.